Energy crisis risk mitigation through Nuclear Power and RES as alternative solutions towards self-sufficiency - George E. Halkos; Argyro Zisiadou (Journal of Risk and Financial Management, 2023)
This paper reviews the case of nuclear energy. Currently, the worldworld is facing one of the greatest energy crises due to the Russo-Ukrainian war. This conflict has lead to limited sources of gas, causing a dramatic decrease in energy supply, leading to emerging energy crisis risks. This is one on the main purposes of reviewing nuclear energy as a possible energy alternative in the future. Apart from presenting the basis of nuclear energy and nuclear reactors, we attempt to compare this source of electricity with other renewable energy forms, such as solar, wind and hydroelectric power. Furthermore, we illustrate the benefits and drawbacks that have been observed regarding nuclear power as well as its contribution to economic growth and the impact it has had on the environment. It has been said that, with the use of nuclear power, air pollution will be reduced because of the elimination of greenhouse gases. However, nuclear power, apart from the final product, generates waste that in this case is radioactive, meaning that the management and disposal techniques are of the utmost importance. Of course, unfortunate events that involved nuclear power do exist and are unfortunately engraved in our memories. Both the nuclear accidents, such as Three Mile Island, Chernobyl and Fukushima, and nuclear weapons usage by military forces, the well-known atomic bombing of Hiroshima and Nagasaki, bring great controversy regarding the adaptation of nuclear power. As is presented in the paper, since the beginning of the new millennium the scheme of energy production and electricity production appears to have changed drastically. By using available data reported by BR, we illustrated that the production of energy and electricity has increased over the last 22 years (2000-2021) due to excessive demand; however, what is more important to mention is the share of both electricity and energy derived from renewable forms such as solar, wind and hydroelectric power. It is shown that more and more countries adopt those sources of energy than did in previous decades. It is crucial to note that it is not the science that causes catastrophic events, but rather the errors of humans.
Keywords: Q01; Q40; Q42; Q52; Q53; 650; renewable energy; energy crisis risks; greenhouse gases emissions; nuclear accidents; nuclear energy; nuclear waste management; nuclear weapons